Reverse Transcription Recombinase Polymerase Amplification Assay for Rapid Detection of Avian Influenza Virus H9N2 HA Gene - Nahed Yehia; Fatma Eldemery; Abdel-Satar Arafa; Ahmed Abd El Wahed; Ahmed El Sanousi; Manfred Weidmann; Mohamed Shalaby (Veterinary Sciences, 2021)
The H9N2 subtype of avian influenza A virus (aIAV) is circulating among birds worldwide, leading to severe economic losses. H9N2 cocirculation with other highly pathogenic aIAVs has the potential to contribute to the rise of new strains with pandemic potential. Therefore, rapid detection of H9 aIAVs infection is crucial to control virus spread. A qualitative reverse transcription recombinase polymerase amplification (RT-RPA) assay for the detection of aIAV subtype H9N2 was developed. All results were compared to the gold standard (real-time reverse transcription polymerase chain reaction (RT-PCR)). The RT-RPA assay was designed to detect the hemagglutinin (HA) gene of H9N2 by testing three pairs of primers and a probe. A serial concentration between 106 and 100 EID50 (50% embryo infective dose)/mL was applied to calculate the analytical sensitivity. The H9 RT-RPA assay was highly sensitive as the lowest concentration point of a standard range at one EID50/mL was detected after 5 to 8 min. The H9N2 RT-RPA assay was highly specific as nucleic acid extracted from H9 negative samples and from other avian pathogens were not cross detected. The diagnostic sensitivity when testing clinical samples was 100% for RT-RPA and RT-PCR. In conclusion, H9N2 RT-RPA is a rapid sensitive and specific assay that easily operable in a portable device for field diagnosis of aIAV H9N2.